2017
DOI: 10.1177/0272684x16685255
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Risk Factors Among Russian Students

Abstract: Purpose To analyze the prevalence of risk factors among Russian students. Methods In this study, 834 students were included from five Federal universities which were localized in four Federal regions of Russian Federation. Future doctors, school teachers, and wellness trainers were included in this study. Students were specifically asked about smoking, physical activity International Physical Activity Questionnaire (IPAQ), and food preference. Waist, hip, weight, and height were measured. Results The region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Besides, students of medical institutes more frequently showed abdominal obesity signs [6]. Results of a quite big (n = 7228) Turkish study showed that in this cohort of mainly middle-aged Turkish doctors, the age-standardized rates of chronic diseases were lower than the rates in the general population except for the rates of hyperlipidemia and coronary artery disease.…”
Section: Resultsmentioning
confidence: 78%
“…Besides, students of medical institutes more frequently showed abdominal obesity signs [6]. Results of a quite big (n = 7228) Turkish study showed that in this cohort of mainly middle-aged Turkish doctors, the age-standardized rates of chronic diseases were lower than the rates in the general population except for the rates of hyperlipidemia and coronary artery disease.…”
Section: Resultsmentioning
confidence: 78%